Characterisation of Pet-related Crimes in the Judicial District of Setúbal since 2014: Factors Conditioning the Applicability of the Law 69/2014 - Cardoso, Catarina Sofia Vieira (2021)
In Portugal, it was in 2014 that crimes of abuse and abandonment of pets were typified, through the Criminal Law nº 69/2014 (articles 387º and 388º), after a long period of “silence” and reflection around these themes. Despite the evolution concerning the animal rights that has occurred over the last few years, it still seems possible to identify gaps that may hamper the application of the Law. Thus, the present study aimed to characterise and understand the crimes of abuse and abandonment of pets, in the District of Setúbal, through a retrospective analysis of almost 6 years (from October 2014 until May 2020), since the publication of the Law in the Diário da República (Official Gazette), in order to identify the system’s strengths and weaknesses, mainly in the sense of identifying necessary improvements. To this end, 39 (10%) dismissed case files were analysed, and semi-structured interviews were applied to 7 professionals with functions related to the protection of pets, including elements of the Public Prosecutor’s Office, elements of the Criminal Police Body, and professionals from Animal Protection Associations. Our results evidenced that Setúbal presents crimes against pets dispersed throughout the district, with the crime of pet abuse being dominant (dogs and cats as the main victims). In a global way, it was possible to identify situations that can be improved, thus being necessary to: i) reformulate the Law, clarifying the concept of pet (e.g., horse is assumed as pet in the dismissed case files, although it was never referred in bibliography as such) and of pet abuse; ii) train the population to be able to identify what crimes of abuse and abandonment really are, reducingthe number of false accusations that unnecessarily mobilise scarce useful resources; iii) increase human and material resources and consequently the means of proof; iv) correctly assign the status of witness in the dismissed case files, distinguishing it from the denouncer; v) better and constantly train police forces and experts to provide better maintenance of the chain of custody; vi) identify the reasons that lead to the practice of these crimes to prevent recurrences and/or practice of other related crimes (e.g., domestic violence); and vii) sensitise the Public Prosecutor to the importance of meticulously filling the dismissed case files with all available information. The application of the suggested improvements will make it possible to fill gaps that are still felt at the local, and eventually national level, contributing to a better and more effective application of the Law.